AFRICA : A 4D Book - Juarez, Christine, 1976-; Della-Rovere, Cynthia; Webber, Clare (North Mankato, Minnesota : Pebble, 2019)
Come along and investigate the continent of Africa. What are its biggest cities? Where is its tallest mountain? What languages do people speak there? Bring augmented reality to your students by downloading the free Capstone 4D app and scanning for access to an online article, video, and discussion questions.
Includes index.
Bibliography : page 23
Keywords: Continents -- Juvenile literature; Africa -- Geography -- Juvenile literature